Confirmatory factor analysis of 12-Item World Health Organization Disability Assessment Schedule in patients with musculoskeletal pain conditions. (May 2017) - Saltychev, Mikhail; Mattie, Ryan; McCormick, Zachary; Laimi, Katri
Objective: To investigate the factor structure of the 12 item World Health Organization Disability Assessment Schedule (WHODAS) 2.0. Design: Cross-sectional cohort survey study. Setting: Physical and Rehabilitation Medicine outpatient university clinic. Subjects: The 408 consecutive patients with chronic musculoskeletal pain. Main measures: Exploratory and confirmatory factor analysis. Results: A two-factor model most accurately fit the observed data of musculoskeletal pain patients (root mean square error of approximation 0.049, relative Chi square value 1.99). Twelve WHODAS 2.0 items were distributed between two factors with covariance between them of 0.8. The first factor contained domains related mostly to physical functioning, while another was associated mostly with social and cognitive functioning. There were a few differences between single items in their importance in defining the variance within these two factors. Of the six International Classification of Functioning, Disability and Health domains belonging to the first construct, the ability to carry out household responsibilities explained most, 84% of the total variance in this construct. For the second factor, the ability to participate in community activities seemed to be the most important, explaining 85% of the total variance in this construct. Conclusions: In this study, the two-factor structure model of the 12-item WODAS 2.0 demonstrated the most accurate fit within patients with musculoskeletal pain conditions.